Khalwat offences in Klang a socio-legal study (1980-85) / Saidatun Nasihah Abdul Rauf - Abdul Rauf, Saidatun Nasihah (Faculty of Law, 1985)
This paper primarily discusses khalwat offences in Klang and jurisdiction of the Syariah Court. The study deals with the real aspect of khalwat in conjunction with the power of the Syariah Court. In the introduction, the writer has discussed the Islamic Attitude towards sexual morality in contrasts with the English Law Attitude. In chapter 2, the meaning of khalwat is discussed. A distinction is made between the meanings under the Islamic concept, under the Selangor Administration of Muslim Law Enactment 1952 and the English law attitude on the subject. The discussion in chapter 3, is on the Islamic Penal law. The criticism of the severity punishments under that law is noted by the writer.